2002
DOI: 10.1246/bcsj.75.1223
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Photolysis of 2-Phenylcycloalkanones with Circularly Polarized Light: A Kinetic Model for Magnetic Field Effects

Abstract: Magnetic field effects (MFE) on asymmetric photolysis involving a biradical intermediate have been investigated on a kinetic model where an intersystem crossing (ISC) of the intermediate is taken into account. Changes in the enantiomeric excesses (ee) of chiral substances with circularly polarized light (CPL) irradiation have been simulated, and the necessary conditions for observing the MFE were obtained. The asymmetric photolysis of racemic 2-phenylcycloalkanones (2-PCAs) with CPL has been carried out in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 41 publications
(110 reference statements)
1
13
0
Order By: Relevance
“…We estimated the recombination yield of 2PCDD in the same manner as reported in our previous paper [18]. This estimation is based on the measurement of time evolution of 2PCDD enantiomers starting from the one optically pure enantiomer.…”
Section: Time Evolution Of Enantiomer Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…We estimated the recombination yield of 2PCDD in the same manner as reported in our previous paper [18]. This estimation is based on the measurement of time evolution of 2PCDD enantiomers starting from the one optically pure enantiomer.…”
Section: Time Evolution Of Enantiomer Concentrationmentioning
confidence: 99%
“…In the presence of molecular oxygen, 2PCAs afford several products through different processes. We have recently reported that the triplet acyl-benzyl biradicals (C 6 -C 8 ) react with molecular oxygen to produce benzoylalkanoic acids, which can be further excited by the UV light, and then subsequent intramolecular hydrogen abstraction (Norrish Type Ⅱ) occurs to produce acetophenone and the corresponding alkenoic acids [18]. Turro et al have observed enhanced 13 C CIDNP signals at carbonyl carbon on the products in 3 the photolysis of 2-phenylcyclododecanone (2PCDD) in aerated solution, in which the presence of an oxidized peroxyester or peracid species has been suggested [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…enantiomeric excesses of substrate and/or product [19][20][21][22]. Michl and coworkers have photolyzed 1-azidoadamantane with circularly polarized light in a low temperature matrix and obtained a chiral cyclic imine having 2% optical purity [23].…”
Section: P H O T O R E a C T I O N S I N I T I A T E D W I T H Circulmentioning
confidence: 99%
“…9 -11 This equation cannot be solved exactly except in special circumstances although numerical methods can be used instead. 11,12 If A is small, however, a situation which usually can be attained by adjusting the concentration of the substrate, (1À10 ÀA )/A c ln10 and a constant. Equation 2 thus becomes…”
mentioning
confidence: 99%